Massively dilated esophagus from long standing achalasia in a female child - Moaied A. Hassan (Elsevier, 2021)
Achalasia is an esophageal motility disorder that is characterized by absence of esophageal peristalsis and failure of the lower esophageal sphincter to relax resulting in abnormal proximal esophageal dilatation. The pathology is rare in pediatric age group with less than 5% of patients present under 15 years of age. Children usually present with dysphagia to solid and liquid foods, and symptoms may progress to chest pain, vomiting, aspiration and weight loss. In children, the pathology is most often misdiagnosed with gastroesophageal reflux disease which leads to a delay in the diagnosis. Definitive diagnosis is established by barium swallow and high resolution esophageal manometry.We present an extremely rare observation of massive dilatation of the esophagus secondary to a long standing achalasia in an eight years old female child. We discuss the mode of presentation as well as the diagnostic and therapeutic approach, and highlight the importance of early diagnosis of this progressive disorder and its impact on management and outcome.